A situation-based multi-agent architecture for handling misunderstandings in interactions - Pham, Thao Phuong; Rabah, Mourad; Estraillier, Pascal (Zielona Góra: Uniwersytet Zielonogórski)
During interactions, system actors may face up misunderstandings when their local states contain inconsistent data about the same fact. Misunderstandings in interactions are likely to reduce interactivity performances (deviation or deadlock) or even affect overall system behavior. In this paper, we characterize misunderstandings in interactions between system actors (that may be human users or system agents) in interactive adaptive systems.
Keywords: interactive adaptive systems; misunderstandings in interactions; situation structuring; consistency management